Existence of Islamic Education in the Contemporary Era Perspective Post Colonial - Nurhalim (Indikator Pendidikan Indonesia, 2022)
The existence of post-colonial Contemporary Islamic education cannot be separated from its historical dynamics in the colonial era, Islamic education was